MANAJEMEN STRATEGI BADAN PENDAPATAN DAERAH PROVINSI RIAU DALAM PENINGKATAN PENDAPATAN PAJAK KENDARAAN BERMOTOR TAHUN 2021 - Zain, Hutri Ziqra; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Motorized vehicles are wheeled vehicles that function to transport people and/or objects that are driven by motors/engines using fuel as energy and can be used on land roads other than rail. Therefore, motorized vehicles are subject to taxation in accordance with statutory regulations, regional regulations and governor's regulations in order to help regional finances from the tax proceeds paid by the community. This research aims to determine the strategic management of the Regional Revenue Agency in increasing motor vehicle tax revenue in 2021 and the factors that influence it through a SWOT analysis which is analyzed according to the Regional Government Strategic Management theory according to Untoro (2010), starting from analyzing the strategy formulation and strategy implementation carried out by the Agency Riau Regional Revenue in an effort to increase registered vehicle tax revenue in 2021, to use influencing factors as correction material to further maximize the potential from the results of the strategic evaluation of the Riau Province Regional Revenue Agency. The data collection technique in this research is in the form of interviews and documentation, with qualitative research methods, namely describing research results from data obtained from the Riau Bapenda regarding the increase in Motor Vehicle Tax (MVT) revenue. So that it provides a clear enough picture to synchronize the causes of motor vehicle tax not reaching the target in 2020 as well as the internal driving and inhibiting factors of Bapenda in increasing MVT income in 2021. Based on the results of three years of research (2019-2021), the growth in MVT income in 2020 dropped drastically to -9.6% from the target of 4.42%, even though the number of motorized vehicles in 2020 increased by 2.1%. The action taken by the Riau Bapenda to increase MVT income in 2021 is to implement a strategic plan by facilitating the expansion of information and improving services in the form of innovative improvements such as expanding Samsat services by adding technical implementation Unit Samsat and wandering around Units, eliminating tax fines, information systems and service applications. Samsat Digital. Keywords: Strategic Management, Improvement, Revenue, Motor Vehicle Tax